Pre-dosing antibody levels and efficacy of thrombolytic drugs containing streptokinase. Issue 3 (September 1994) - Gemmill, J D; Hogg, K J; Dunn, F G; Rae, A P; Hillis, W S
Abstract : OBJECTIVE--To evaluate the influence of pretreatment streptokinase resistance titre and the concentration of IgG antibodies to streptokinase on the efficacy of thrombolytic drugs containing streptokinase in restoring coronary patency in acute myocardial infarction. DESIGN--Comparative observational study. SETTING--City general hospital. PATIENTS--One hundred and twenty four previously unexposed patients presenting within six hours of onset of acute myocardial infarction. INTERVENTIONS--Streptokinase, 1.5 MIU as intravenous infusion over 60 minutes (60 patients), or anistreplase, 30 units as intravenous injection over five minutes (64 patients). MAIN OUTCOME MEASURES--Pretreatment streptokinase resistance titre and concentration of IgG antibodies to streptokinase were measured in 96 and 124 patients respectively and coronary patency assessed angiographically at 90 minutes and 24 hours. RESULTS--Pretreatment streptokinase resistance titre and concentrations of IgG antibodies to streptokinase were low and skewed towards higher values. Those patients with coronary occlusion at 24 hours had a significantly higher median streptokinase resistance titre (100 v 50 streptokinase IU ml-1, P = 0.02). There were trends towards a higher streptokinase resistance titre in those patients with coronary occlusion at 90 minutes (50 v 20 streptokinase IU ml-1, P = 0.06) and higher concentrations of IgG antibodies to streptokinase in those with coronary occlusion at both 90 minutes and 24 hours (1.53 v 0.925, P = 0.03; 1.65 v 1.04 micrograms streptokinase binding ml-1, P = 0.06). Coronary patency rates were similar in the two treatment groups. CONCLUSIONS--In the range measured in previously unexposed patients the streptokinase resistance titre has a small, but significant, negative influence on the efficacy of streptokinase and anistreplase. This effect should be considered if retreatment with streptokinase or anistreplase is proposed.